Self-Treatment of Posterior Canal Benign Paroxysmal Positional Vertigo: A Preliminary Study - Gan, Zhuangqin; Zhou, Shiling; Yang, Hui; He, Feng; Wei, Dong; Bai, Ya; Wang, Yuanyuan; Wang, Yingxia; Fu, Wei; Han, Junliang (Frontiers in Medicine, 2021)
Objectives: The purpose of this study is to investigate a modified Epley maneuver for self-treatment of posterior canal benign paroxysmal positional vertigo (PC-BPPV). Methods: The study recruited 155 patients with PC-BPPV. All patients were randomized into the Epley maneuver group (n = 77) and modified Epley maneuver group (n = 78). We analyzed the resolution rate (1 day and 1 week), residual symptoms after the maneuver, and adverse effects. Results: It was found that the modified Epley maneuver group had a higher resolution rate than that of the Epley maneuver group in the treatment of PC-BPPV after 1 day of the initial maneuver (p < 0.05). However, there was no difference in resolution rate between the Epley maneuver group and the modified Epley maneuver group in resolution rate after 1 week of the initial maneuver (p > 0.05). The modified Epley maneuver group had fewer residual symptoms than that of the Epley maneuver group 1 week after treatment of PC-BPPV (p < 0.05). Significant improvements were also observed in average DHI scores in patients who underwent the modified Epley maneuver compared to the Epley maneuver (p < 0.05). There was no significant difference in adverse effects between the two groups (p > 0.05). Conclusions: The modified Epley maneuver has a satisfactory therapeutic efficacy with less residual symptoms and could be recommended as a self-treatment for patients with PC-BPPV.